Willingness-to-pay and free-riding in a national energy efficiency retrofit grant scheme: A revealed preference approach - Matthew Collins; John A. Curtis (The Economic and Social Research Institute (ESRI), 2016)
Understanding the drivers of energy efficient behaviour in the household can provide significant insights on how best to provide incentives for homes to engage in energy efficiency retrofits. This can have wide-reaching effects in reducing the demand for energy and in turn reducing carbon emissions. Many national grant aid schemes exist to support homes in engaging in retrofits, but these can also be availed of by free-riders, which are homes that would engage in a retrofit even in the absence of financial support. This paper explores retrofit choice, willingness-to-pay for retrofit works and free-riding in a grant aid scheme for residential energy efficiency retrofits. Household preferences are revealed through energy efficiency retrofits undertaken by Irish home owners, after having been presented with an array of retrofit measures and combinations thereof. We use a McFadden's choice model to estimate willingness-to-pay for energy efficiency renovation works using revealed preference data (McFadden, 1984). The results of this analysis are then used to estimate the extent to which freeriding has occurred in the scheme to date. We find that less efficient and larger homes are willing to pay more for energy efficiency improvements, and find that households which had previously engaged in a retrofit via the grant scheme were willing to pay over twice as much as those retrofitting for the first time. Free-riding varies by retrofit measure, with solar collector retrofits possessing close to zero free-riders, while free-riders comprised over 33% of heating controls retrofits.
Keywords: D12; Q48; 330; willingness to pay; free-riders; energy efficiency retrofit; revealed preferences